(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The increasing threat of plant diseases poses a significant challenge to global food security. Rapid and accurate identification of plant diseases is crucial for effective disease management and prevention. In recent years, deep learning techniques have shown great promise in automating the process of plant disease identification through image analysis. This report presents a comprehensive study on image-based plant disease classification using deep learning techniques. The report begins by providing an overview of plant diseases and their impact on agriculture. It discusses the limitations of traditional disease identification methods and highlights the potential of deep learning algorithms in revolutionizing the field. The importance of image-based approaches is emphasized due to their non-destructive and scalable nature. Next, the report delves into the methodology of deep learning for plant disease classification. It explores various architectures such as convolutional neural networks (CNNs) and their variants, including transfer learning and ensemble methods. The training process, data augmentation techniques, and hyperparameter tuning are discussed in detail.